2021
DOI: 10.3390/ijms22094666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin and Its Different Formulations in Preclinical and Clinical Studies of Peripheral Neuropathic and Postoperative Pain: A Comprehensive Review

Abstract: Lesion or disease of the somatosensory system leads to the development of neuropathic pain. Peripheral neuropathic pain encompasses damage or injury of the peripheral nervous system. On the other hand, 10–15% of individuals suffer from acute postoperative pain followed by persistent pain after undergoing surgeries. Antidepressants, anticonvulsants, baclofen, and clonidine are used to treat peripheral neuropathy, whereas opioids are used to treat postoperative pain. The negative effects associated with these dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 211 publications
(328 reference statements)
1
18
0
Order By: Relevance
“…It has been shown that curcumin upregulates endogenous cellular antioxidant pathways which include increase in expression of cytoprotective quinone oxidoreductase 1 (NQO1), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1(HO-1), Nrf2-induced target genes in primary spinal cord astrocytes, decreases the level of intracellular ROS, and attenuates oxidative damage and mitochondrial dysfunction. 12,30,44,45 Recent studies on curcumin as possible antinociceptive agent along with the results of the present study further supports the therapeutic potential of curcumin in alleviating neuropathic pain.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been shown that curcumin upregulates endogenous cellular antioxidant pathways which include increase in expression of cytoprotective quinone oxidoreductase 1 (NQO1), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1(HO-1), Nrf2-induced target genes in primary spinal cord astrocytes, decreases the level of intracellular ROS, and attenuates oxidative damage and mitochondrial dysfunction. 12,30,44,45 Recent studies on curcumin as possible antinociceptive agent along with the results of the present study further supports the therapeutic potential of curcumin in alleviating neuropathic pain.…”
Section: Discussionsupporting
confidence: 82%
“…Curcumin is a major bioactive component of turmeric, which has been demonstrated to have a variety of biological activities, including antitumour and antioxidant actions. 12 Emerging experimental evidence indicates that curcumin has analgesic effect plausibly by diminishing the harmful effects of oxidative stress in neuropathic pain induced by oxaliplatin and diabetes. 13,14 Further, it is also a potent inhibitor of the mitogen-activated protein kinases (MAPKs) and NF-κB, which are critical in the transcriptional regulation of proinflammatory cytokine gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when considering the results of this and previous studies, we propose that curcumin ameliorates cisplatin-induced oxidative stress and cytotoxicity in endothelial cells and pericytes, leading to restoration of tight junction proteins and BNB functions. Apart from chemotherapy-induced neuropathy, increasing evidence supports the beneficial effects of curcumin on neuropathies from various etiologies [32]. However, whether curcumin can alleviate cisplatin-induced neuropathy in patients remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Use of antioxidant compounds, such as vitamin E [ 28 , 29 ], glutathione [ 30 ] and N-acetylcysteine [ 31 , 32 ] and, recently, antioxidant molecules such as the novel BPF-15 [ 33 ] and a-lipoic acid [ 32 ] along with oxaliplatin treatment has been found to have beneficial effects in induced PN. The use of natural occurring antioxidant agents, such as polyphenol and catechins rich green tea [ 34 ], polyphenol rich curcumin, isolated from the turmeric plant Curcuma longa [ 35 , 36 ] and cilibinin, found in seeds of the milk thistle ( Silybum marianum ) [ 26 ] were also proven to have significant protective effects towards evoked PN.…”
Section: Introductionmentioning
confidence: 99%